(untitled) (Journal of Comparative Social Work, 2023)
In high-income countries, population ageing has a significant impact on the labour force and care demands. As a result, the tendency is to rely on migrant workers to meet workforce and care demands. Drawing on insights from Bronfenbrenner’s ecological systems theory, this study focused on unskilled migrant healthcare assistants in Norway’s long-term care. The objectives were to explore factors influencing the decision of unskilled migrant healthcare assistants to work in elderly care, sources of knowledge about work in elderly care, and challenges encountered in elderly care work. The key research questions were as follows: a) What factors influence the decision of migrant healthcare assistants to work in elderly care? b) What are the sources of knowledge/information about work in elderly care for migrant healthcare assistants? c) What are some of the challenges of working in elderly care for migrant healthcare assistants? Qualitative research and purposive sampling were used to recruit 20 participants: 13 unskilled migrant healthcare assistants and seven managers of long-term care facilities in South-Eastern and Northern Norway. Data were collected using in-depth individual interviews, focus group discussions and participant observation, and thematically analysed. Findings indicated that factors influencing unskilled migrant healthcare assistants’ decision to work in the elderly care sector included cultural norms and values of caring for older people, nonrecognition of overseas qualifications and economic considerations. State-organized language learning programmes, Norwegian Labour and Welfare Administration (NAV) offices, as well as migrant family and community networks, provided crucial information about work in elderly care. Challenges regarding lack of career progression, temporary working contracts, low status and poor wages emerged. In conclusion, meaningful employment outcome through better opportunities for career progression are essential for unskilled migrant healthcare assistants’ well-being and care for older people. It would be useful for long-term care policymakers and stakeholders to address the challenges faced by its aged care workforce.